Validation and comparison of several global geopotential models with an official quasigeoid solution of Serbia - Stanković, Marko D. (Geodetski vestnik, 2022)
This study aims to analyze the quality of several local reference quasigeoid surfaces obtained from several Global Geopotential Models (GGM) relative to the official quasigeoid solution of Serbia (SQM2011) and GNSS/dh observations for the territory of Serbia. Therefore, validation and comparison of the derived surfaces from the three GGM’s were made based on comparisons of height anomaly derived from GGM’s, SQM2011, and the GNSS/dh observations at the points of the high-precision leveling network. The selected publicly available GGM’s in this study are GOCO05c, SGGUGM-2, and XGM2019e. Primarily, at 1001 points of the high-precision leveling network, the differences between GGM and GNSS/dh height anomaly were calculated. The final translation parameters were calculated in the iteration procedure, which was then used to calculate the final values of the estimated height anomaly for all GGM’s at 143207 points of the regular grid of spatial resolution 0.5' × 0.5' on the entire territory of Serbia. From the estimated height anomaly, three GGM-derived surfaces were modeled relative to the SQM2011. According to the results of the calculations, SGG-UGM-2 provides the best approximation of the quasigeoid SQM2011, where the remaining differences have a mean value of 0.01 m, a standard deviation of 0.06 m, and a span of 0.67 m.
Keywords: anomalije višin; Global Geopotential Model; globalni geopotencialni model; GNSS/dh; gravitacija; gravity; height anomalies; kvazigeoid; quasigeoid